Detection of disk-jet coprecession in a tidal disruption event - Wang, Yanan; Lin, Zikun; Wu, Linhui; Lei, Wei-Hua; Wei, Shuyuan; Zhang, Shuang-Nan; Ji, Long; del Palacio, Santiago; Baldi, Ranieri D.; Huang, Yang; Liu, Ji-Feng; Zhang, Bing; et al. (American Association for the Advancement of Science (AAAS), 2026)
Theories and simulations predict that intense space-time curvature near black holes bends the trajectories of light and matter, driving disk and jet precession under relativistic torques. However, direct observational evidence of disk-jet coprecession remains elusive. Here, we report the most compelling case to date: a tidal disruption event (TDE) exhibiting unprecedented 19.6-day quasi-periodic variations in both x-rays and radio, with x-ray amplitudes exceeding an order of magnitude. The nearly synchronized x-ray and radio variations suggest a shared mechanism regulating the emission regions. We demonstrate that a disk-jet Lense-Thirring precession model successfully reproduces these variations while requiring a low-spin black hole. This study uncovers previously uncharted short-term radio variability in TDEs, highlights the transformative potential of high-cadence radio monitoring, and offers profound insights into disk-jet physics.